Use of cannabinoids as a therapeutic perspective for psoriasis vulgaris: an integrative review (Research, Society and Development, 2022)
Psoriasis is a chronic pathology with rapid proliferation in the skin, it is not contagious and shows signs of inflammation. In it, the immune system attacks the cells of the dermis, and for this reason it is an autoimmune disease favoring the appearance of scaly lesions, with the presence of erythema and irregular shapes. Considering this, this integrative literature review aims to understand the use of the Cannabis sativa plant as a therapeutic perspective for psoriasis vulgaris. For this, a search on the subject was carried out in the Scientific Electronic Library Online (SciELO), U.S National Library of Medicine National Institutes of Health (PubMed) and Academic Google databases, the inclusion rules were: text available in its entirety; articles published in the last decade, prioritizing the most recent ones; written in Portuguese, English or Spanish and, finally, be directly related to the object of study presented here. It was found that cannabinoids have great potential in the treatment of psoriasis, with their mechanism of action focused on the main pathogenic pathways of the disease: keratogenesis, inflammation and angiogenesis, however studies are mostly in vitro. More clinical trials in humans and studies are needed to clarify the toxicity, safety and efficacy of cannabinoids in the treatment of the disease in question.